UPAYA PENINGKATAN PEMAHAMAN MEMBACA SISWA KELAS XII IPA 1 SMAN 1 PASAMAN DALAM TEKS “DISCUSSION” MELALUI TEKHNIK BERDEBAT - Abdi, Haswinda (STKIP Pesisir Selatan, 2017)
Based on the assessment of learning outcomes in the English lesson about reading reading text that genre